2017
DOI: 10.1111/ppl.12531
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is involved in methane‐induced adventitious root formation in cucumber

Abstract: Our previous studies revealed that methane (CH ) induces adventitious rooting in cucumber. However, the corresponding molecular mechanism is still elusive. In this work, we discovered that CH triggered the accumulation of nitric oxide (NO) and thereafter cucumber adventitious rooting, mimicking the inducing effects of sodium nitroprusside (SNP) and NONOate (two NO-releasing compounds). Above mentioned responses were sensitive to NO scavenger(s), showing that the accumulation of NO and adventitious root develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 45 publications
(87 reference statements)
2
39
0
Order By: Relevance
“…Cross sections (3 mm thick) were cut from stems of viruliferous or nonviruliferous SBPH-inoculated rice plants, infiltrated with an NO fluorescent probe (10 μM 4amino-5-methyl-amino-2′,7′-di-fluorofluorescein diacetate [DAF-FM DA]) diluted in a 20 mM Hepes-NaOH buffer, pH 7.2, followed by 15 min incubation in the dark [27,28].…”
Section: Quantification Of No Content By Laser Scanning Confocal Micrmentioning
confidence: 99%
“…Cross sections (3 mm thick) were cut from stems of viruliferous or nonviruliferous SBPH-inoculated rice plants, infiltrated with an NO fluorescent probe (10 μM 4amino-5-methyl-amino-2′,7′-di-fluorofluorescein diacetate [DAF-FM DA]) diluted in a 20 mM Hepes-NaOH buffer, pH 7.2, followed by 15 min incubation in the dark [27,28].…”
Section: Quantification Of No Content By Laser Scanning Confocal Micrmentioning
confidence: 99%
“…Among these, NO, a free radical gas, has been shown to have multiple physiological functions in plants [28,29]. Besides the enhancement of plant adaptation against stresses, the functions of NO include the promotion of root hair development, adventitious rooting, and lateral root formation [30][31][32][33], although the enzymatic resource(s) of NO biosynthesis in those aforesaid processes remains elusive. In animals, the synthesis of NO from L-arginine is catalyzed by the heme-containing enzyme nitric oxide synthase (NOS) [34].…”
Section: Introductionmentioning
confidence: 99%
“…BR Z reduced the production of NO and activities of NOS-like and NR, and its effect was timedependent. Previous studies also showed that methane (CH 4 ) triggered the accumulation of NO in cucumber during adventitious root formation [57]. Ethephon treatments induced the increase of endogenous NO level and significantly improved activities of NOS-like and NR during adventitious rooting [58].…”
Section: Discussionmentioning
confidence: 93%